2017
DOI: 10.1289/ehp41
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Effects of Future Atmospheric CO2 Concentrations on Protein Intake and the Risk of Protein Deficiency by Country and Region

Abstract: Background:Crops grown under elevated atmospheric CO2 concentrations (eCO2) contain less protein. Crops particularly affected include rice and wheat, which are primary sources of dietary protein for many countries.Objectives:We aimed to estimate global and country-specific risks of protein deficiency attributable to anthropogenic CO2 emissions by 2050.Methods:To model per capita protein intake in countries around the world under eCO2, we first established the effect size of eCO2 on the protein concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(107 citation statements)
references
References 37 publications
0
101
0
Order By: Relevance
“…The nutritional quality of global cereal production has declined steadily with time, as nutrient‐rich cereals have been supplanted by high‐yielding rice, wheat, and maize varieties (DeFries et al, ; Medek et al, ). This increase in high‐yielding crop production has been in part driven by the increasing prevalence of large farms, which generally produce a less nutritionally diverse set of crops (Herrero, et al, ), and has resulted in dwindling amounts of key nutrients, such as protein, iron, and zinc per tons of cereal crop (DeFries et al, ).…”
Section: The Food Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional quality of global cereal production has declined steadily with time, as nutrient‐rich cereals have been supplanted by high‐yielding rice, wheat, and maize varieties (DeFries et al, ; Medek et al, ). This increase in high‐yielding crop production has been in part driven by the increasing prevalence of large farms, which generally produce a less nutritionally diverse set of crops (Herrero, et al, ), and has resulted in dwindling amounts of key nutrients, such as protein, iron, and zinc per tons of cereal crop (DeFries et al, ).…”
Section: The Food Systemmentioning
confidence: 99%
“…The nutritional quality of global cereal production has declined steadily with time, as nutrient-rich cereals have been supplanted by high-yielding rice, wheat, and maize varieties (DeFries et al, 2016;Medek et al, 2017). This increase in high-yielding crop production has been in part driven by the increasing prevalence 10.1029/2017RG000591…”
Section: Environmental and Climate Constraints On Food Productionmentioning
confidence: 99%
“…Physiological zinc requirements were estimated by the International Zinc Nutrition Consultative Group (IZiNCG) et al (2004). We estimated protein requirements following a methodology first used by Medek et al (2017) and refined by Smith and Myers (2018 For nearly all nutrients for which we estimate the risk of deficiency, the requirements for pregnant and lactating women are greater than those of non-pregnant or non-lactating women of the same age. The only exception is calcium for lactating women, for which the requirement is the same as for nonlactating women.…”
Section: Estimated Average Requirements (Ears)mentioning
confidence: 99%
“…Interestingly, meta-analyses for a range of crop species have shown that future increases to atmospheric CO 2 will also impact the nutritional protein content of crops 10 as well as minerals such as zinc and iron. [10][11][12] Hence, to maintain or improve an individual's nutritional profile, it will remain important to make available additional varieties of nutrient-rich foods, such as meat, dairy, fish, nutrient-rich vegetables/legumes and fortified products, but in a more feasible manner for the environment than that of the current food and agriculture system. Sustainable agricultural practices should also focus on the rehabilitation of degraded soils, which limit agricultural productivity and in some parts of the world is a driving force in the conversion of pristine environments to agriculture uses.…”
Section: Farmingmentioning
confidence: 99%